The limits of the forgiveness in international relations: groups supporting the Yasukuni shrine in Japan and political tensions in East Asia - Álvarez, María del Pilar (2016)
Visits (or attempts to visit) to the Yasukuni Shrine by Japanese officials have generated a series of controversies and tensions between the countries occupied by imperialist Japan during the Pacific War. The central dilemma is that Yasukuni, emblem of Japanese militarism, questions the coherence and consistency of the requests for forgiveness made by different Japanese prime ministers to countries in the region in repentance for atrocities and violations of human rights committed in the past. The weakness of the apologies is not an exclusive problem of Japan. On the contrary, the official pardon granted by one state to another has become an increasingly common practice, but questioned in international relations. The limits of apologies in the process of reconciliation between states have led to a new research strand, aligned with the debates on transitional justice, which discusses dimensions of the level of forgiveness in terms of rectification processes. From this perspective, previous research shows that there is a tendency to analyse the case of Yasukuni without delving into the social groups that support the shrine and define the agenda of prominent personalities of local politics, especially linked to the ruling party, the Liberal Democratic Party (LDP), who claim Yasukuni. Faced with this gap, this article examines the characteristics and modes of action of the groups in favour of Yasukuni and the responses from China and South Korea to the visits to the shrine by officials, in order to understand the peculiarities and scope of forgiveness in East Asia.